Atrial Premature Beats Predict Atrial Fibrillation in Cryptogenic Stroke: Results From the EMBRACE Trial. Issue 4 (April 2015) - Gladstone, David J.; Dorian, Paul; Spring, Melanie; Panzov, Val; Mamdani, Muhammad; Healey, Jeff S.; Thorpe, Kevin E.; Aviv, R.; Boyle, K.; Blakely, J.; Cote, R.; Hall, J.; et al.
Abstract : Background and Purpose—: Many ischemic strokes or transient ischemic attacks are labeled cryptogenic but may have undetected atrial fibrillation (AF). We sought to identify those most likely to have subclinical AF. Methods—: We prospectively studied patients with cryptogenic stroke or transient ischemic attack aged ≥55 years in sinus rhythm, without known AF, enrolled in the intervention arm of the 30 Day Event Monitoring Belt for Recording Atrial Fibrillation After a Cerebral Ischemic Event (EMBRACE) trial. Participants underwent baseline 24-hour Holter ECG poststroke; if AF was not detected, they were randomly assigned to 30-day ECG monitoring with an AF auto-detect external loop recorder. Multivariable logistic regression assessed the association between baseline variables (Holter-detected atrial premature beats [APBs], runs of atrial tachycardia, age, and left atrial enlargement) and subsequent AF detection. Results—: Among 237 participants, the median baseline Holter APB count/24 h was 629 (interquartile range, 142–1973) among those who subsequently had AF detected versus 45 (interquartile range, 14–250) in those without AF ( P <0.001). APB count was the only significant predictor of AF detection by 30-day ECG ( P <0.0001), and at 90 days ( P =0.0017) and 2 years ( P =0.0027). Compared with the 16% overall 90-day AF detection rate, the probability of AF increased from <9% among patients with <100 APBs/24 h to 9% to 24% in those with 100 to 499 APBs/24 h, 25% to 37% with 500 to 999 APBs/24 h, 37% to 40% with 1000 to 1499 APBs/24 h, and 40% beyond 1500 APBs/24 h. Conclusions—: Among older cryptogenic stroke or transient ischemic attack patients, the number of APBs on a routine 24-hour Holter ECG was a strong dose-dependent independent predictor of prevalent subclinical AF. Those with frequent APBs have a high probability of AF and represent ideal candidates for prolonged ECG monitoring for AF detection. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00846924. Abstract : Supplemental Digital Content is available in the text.